A gallium nitride-based semiconductor laser epitaxial structure for improving uniformity of quantum well indium composition and a method for manufacturing the same

CN121192512BActive Publication Date: 2026-10-09Shandong Huaguang Optoelectronics Co. Ltd.
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511075563.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-01
Publication Date
2026-10-09
Estimated Expiration
2045-08-01

AI Technical Summary

Technical Problem

但该方法只是通过外部层的应力作用来部分的抑制相分离,无法从量子阱这一关键层的材料生长角度来从根本上解决

Benefits of technology

[0049] 1. This invention introduces trace amounts of aluminum atoms during the growth of the quantum well layer, suppressing the aggregation effect of indium atoms in the quantum well. This significantly improves the luminescence uniformity of the quantum well layer, reduces the full width at half maximum (FWHM) of the emission spectrum, and increases the peak gain of the laser device. Figure 4 It can be seen that the photoluminescence (PL) full width at half maximum (FWHM) of the gallium nitride green laser epitaxial wafer fabricated using this invention is reduced by 12 nm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121192512B_ABST
    Figure CN121192512B_ABST
Patent Text Reader

Abstract

The application relates to a gallium nitride-based semiconductor laser epitaxial structure for improving the uniformity of quantum well indium components and a preparation method, and belongs to the technical field of semiconductor lasers. From bottom to top, the structure comprises a substrate, a first limiting layer, a first waveguide layer, an active region, a second waveguide layer, an electron blocking layer, a second limiting layer and a contact layer. When growing high-indium-component quantum wells, a small amount of trimethylaluminum is introduced into the active region of the application, the surface inhibitor effect of aluminum atoms is utilized to inhibit the aggregation of indium atoms on the growth surface, the indium atoms are promoted to be quickly and uniformly incorporated into the epitaxial material, the indium atoms are more uniformly distributed in the quantum wells, and therefore, the quantum well structure with consistent light-emitting wavelengths and high peak gain is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an epitaxial structure and fabrication method for a gallium nitride-based semiconductor laser that improves the uniformity of indium composition in a quantum well, belonging to the field of semiconductor laser technology. Background Technology

[0002] Semiconductor lasers possess advantages such as small size, high efficiency, good stability, long lifespan, and simple and compact structure, and are widely used in industrial processing, communications, medical applications, weaponry, ranging, and high-density optical storage. However, due to the limitations of the band structure, traditional first- and second-generation semiconductors could only produce semiconductor lasers with wavelengths up to the red light band. It was not until the processing technology of third-generation semiconductors such as gallium nitride (GaN), zinc oxide (ZnO), and silicon carbide (SiC) matured that short-wavelength blue-green lasers were gradually developed and entered the market. Gallium nitride (GaN) materials occupy a more important position in optoelectronic devices. Gallium nitride (GaN) and gallium nitride-based materials formed with aluminum nitride (AlN) and indium nitride (InN) are direct bandgap semiconductors with very high radiative recombination efficiency. Furthermore, their emission wavelengths cover a wide spectral range from infrared to ultraviolet, making them the preferred material for manufacturing semiconductor lasers, especially blue-green, violet, and ultraviolet lasers.

[0003] Semiconductor lasers are a type of laser, and to achieve laser output, three conditions must be met: first, a resonant cavity must be present; second, population inversion must be achieved; and third, the gain must be greater than the absorption. The resonant cavity in a semiconductor laser is typically constructed from naturally cleaved crystal planes, and a high-reflectivity coating can be applied to improve reflectivity. Population inversion is usually achieved by increasing the injection current, and a necessary condition is that the quasi-Fermi level difference between electrons and holes must be greater than the laser photon energy. The first two conditions are relatively easy to achieve, and their parameters are relatively easy to adjust; for example, the number of laser photons emitted can be adjusted by changing the cavity surface reflectivity, and the output power can be adjusted by changing the current. However, the gain parameter, the third condition, is closely related to the semiconductor material and structural design, especially the physical properties of the material, which have the greatest impact on the gain spectrum. For example, in gallium nitride-based blue and green lasers, although their epitaxial structures are similar, the electro-optical conversion efficiencies of blue and green lasers differ significantly. Currently, the best blue light conversion efficiency exceeds 50%, while the green laser's conversion efficiency has only just reached 20%. A major reason for this huge difference is the gain coefficient of the InGaN quantum well. For example, the quantum well of a green laser requires a higher indium content and needs to be grown at a lower temperature, resulting in poorer crystal quality and reduced gain. Furthermore, according to a literature report (OPTICS EXPRESS, Vol. 15, No. 12, 7730), as the indium content increases, phase analysis of the InGaN material causes inhomogeneity in the indium composition, ultimately leading to gain spectrum broadening and a decrease in peak gain.

[0004] To address the peak gain reduction problem caused by indium composition inhomogeneity, Chinese patent document CN116598893A discloses a semiconductor laser with an InN phase separation suppression layer. This layer, with an indium composition lower than that of the quantum well in the active region, acts as a transition layer, partially suppressing phase separation and improving indium composition uniformity. However, this method only partially suppresses phase separation through the stress of the external layer and cannot fundamentally solve the problem from the perspective of the material growth of the crucial quantum well layer. Therefore, it is necessary to find a material growth scheme for the InGaN quantum well to fundamentally solve the indium composition uniformity problem and improve peak gain. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a gallium nitride-based semiconductor laser epitaxial structure that improves the uniformity of indium composition in quantum wells. A small amount of trimethylaluminum is introduced during the growth of the high-indium-composition quantum well. Utilizing the surface inhibitory effect of aluminum atoms, the aggregation of indium atoms within the growth surface is suppressed, promoting rapid and uniform incorporation of indium atoms into the epitaxial material. This results in a more uniform distribution of indium atoms within the quantum well, thereby achieving a quantum well structure with consistent emission wavelength and high peak gain. The underlying principle is based on the different binding energies of the chemical bonds in gallium nitride, indium nitride, and aluminum nitride, where the binding energy of gallium nitride is 8.9 eV, indium nitride is 7.7 eV, and aluminum nitride is 11.9 eV. During high-temperature growth of the quantum well material, due to the relatively weak binding energy between indium atoms and the crystal, indium atoms are more likely to migrate to regions with higher indium composition on the quantum well surface, further exacerbating the non-uniformity of the quantum well composition. Introducing a small amount of aluminum atoms during growth, due to their stronger binding energy, allows aluminum atoms to rapidly incorporate into the lattice, suppressing the migration of surface indium atoms and thus improving the compositional uniformity of the quantum well.

[0006] The present invention also provides a method for fabricating the above-mentioned gallium nitride-based semiconductor laser epitaxial structure with improved indium composition uniformity of quantum well.

[0007] The technical solution of the present invention is as follows:

[0008] An epitaxial structure for a gallium nitride-based semiconductor laser that improves the uniformity of indium composition in a quantum well includes, from bottom to top, a substrate, a first confinement layer, a first waveguide layer, an active region, a second waveguide layer, an electron blocking layer, a second confinement layer, and a contact layer;

[0009] The active region is In z Ga 1-z The N / GaN quantum well structure comprises three GaN barrier layers and two In... z Ga 1-z N quantum well layer, GaN barrier layer and In z Ga 1-z N quantum well layers are grown alternately, that is, each In zGa 1-z The N-quantum well layer is flanked by GaN barrier layers, In z Ga 1-z The N quantum well layer contains Al atoms.

[0010] According to a preferred embodiment of the present invention, In z Ga 1-z The Al atom concentration in the N quantum well layer ranges from 5E18 to 5E19 / cm³. 3 The Al atomic content can be determined by secondary ion mass spectrometry (SIMS), and the atomic ratio in the crystal is about 1‰.

[0011] According to a preferred embodiment of the present invention, when the emission band is blue light, the active region thickness is 25-45 Å and the In composition is 0.15-0.25; when the emission band is green light, the active region thickness is 20-35 Å and the indium composition is 0.20-0.35.

[0012] According to a preferred embodiment of the present invention, the first confinement layer consists of a first confinement layer A and a first confinement layer B from bottom to top, and the material of the first confinement layer A is Al. x1 Ga 1-x1 N, x1 is 0.01 to 0.1, thickness is 0.8 to 2 micrometers, dopant is silicon, and doping concentration is 1E18 to 1E19 / cm. 3 ;

[0013] The first confinement layer B is made of GaN with a thickness of 0.2–0.5 micrometers, and the dopant element is silicon with a doping concentration of 1E18–1E19 / cm³. 3 .

[0014] According to a further preferred embodiment of the present invention, the first confinement layer A has a x1 of 0.04 to 0.08, a thickness of 1 to 1.5 micrometers, and a doping concentration of 3E18 to 5E18 / cm. 3 ;

[0015] The thickness of the first confinement layer B is 0.2–0.3 micrometers, and the doping concentration is 3E18–5E18 / cm². 3 .

[0016] According to a preferred embodiment of the present invention, the substrate is gallium nitride, silicon carbide, or zinc oxide, etc., and the substrate conductivity type is n-type.

[0017] The first waveguide layer material is In. y1 Ga 1-y1 The nitrogen (N) layer has a thickness of 0.05–0.5 micrometers and is doped with silicon at a concentration of 1E18–1E19 / cm². 3The average value of y1 in the first waveguide layer is 0.03 to 0.08, and the indium content gradually increases, with the direction of increase from the first confinement layer to the active region. The indium content gradually increases from 0.01 to 0.06 to 0.09.

[0018] The second waveguide layer is made of In. y2 Ga 1-y2 N, with a thickness of 0.05 to 0.5 micrometers, the average value of y2 in the second waveguide layer is 0.02 to 0.07, the indium content gradually decreases, and the decreasing direction is from the active region to the second confinement layer. The indium content gradually decreases from 0.05 to 0.08 to 0.005.

[0019] The electron blocking layer material is Al x2 Ga 1-x2 The N, x2 range is 0.10–0.30, the thickness is 5–50 nm, the dopant element is magnesium, and the doping concentration is 2E18–3E19 / cm². 3 ;

[0020] The second confinement layer is made of Al material. x3 Ga 1-x3 The N, x3 range is 0.01–0.09, the thickness is 0.2–0.8 micrometers, the dopant element is magnesium, and the doping concentration is 5E17–3E19 / cm³. 3 ;

[0021] The contact layer material is GaN, with a thickness of 5–100 nanometers, and the doping element is magnesium, with a doping concentration of 2E19–1E20 / cm. 3 .

[0022] According to a further preferred embodiment of the present invention, the thickness of the first waveguide layer is 0.2-0.3 micrometers;

[0023] The electron blocking layer has a x² value of 0.15–0.25 and a thickness of 8–20 nanometers.

[0024] The second confinement layer has a x3 of 0.03–0.06 μm and a thickness of 0.3–0.7 μm, with a doping concentration of 1E18–1E19 / cm². 3 ;

[0025] The contact layer thickness is 10–20 nanometers.

[0026] The above-mentioned method for fabricating gallium nitride-based semiconductor laser epitaxial structures with improved indium composition uniformity in quantum wells comprises the following steps:

[0027] (1) Growth of the first confinement layer:

[0028] Using an MOCVD device, the substrate is placed in the device, and nitrogen and hydrogen are introduced as carrier gases, while ammonia is introduced as a reaction gas to provide a nitrogen source. First, trimethylgallium and trimethylaluminum are introduced to grow the first confinement layer A; then trimethylaluminum is turned off to grow the first confinement layer B. Silane is used as an n-type doping source. After the growth of the first confinement layer is completed, trimethylgallium and trimethylaluminum are turned off.

[0029] (2) Growth of the first waveguide layer:

[0030] Trimethylindium and triethylgallium are introduced, and the indium composition and distribution of the first waveguide layer are controlled by the flow rate of trimethylindium or the growth temperature. When the flow rate of trimethylindium decreases, the indium composition in the waveguide layer decreases, and when the growth temperature decreases, the indium composition in the waveguide layer increases. The first waveguide layer confinement layer uses silane as an n-type dopant source.

[0031] (3) Growth in the active region:

[0032] Indium is grown by introducing trimethylindium and triethylgallium. z Ga 1-z In the N-quantum well layer, during the growth of the GaN barrier layer, only triethylgallium is introduced. The indium composition is controlled by the flow rate of trimethylindium or the growth temperature during In growth. z Ga 1-z When creating an N quantum well layer, a small amount of trimethylaluminum is introduced; for example, in a metal-organic chemical vapor deposition apparatus, In is grown... z Ga 1-z For N-quantum well layers, the flow rates of triethylgallium and trimethylaluminum are 50 μmol / min and 1 μmol / min, respectively (the above flow rates are for reference only, and the flow rates may vary greatly depending on the structure, wavelength, or epitaxial growth equipment).

[0033] (4) Growth of the second waveguide layer:

[0034] A second waveguide layer is grown by introducing trimethylindium and triethylgallium. The indium composition and its distribution in the waveguide layer are controlled by the flow rate of trimethylindium or the growth temperature.

[0035] (5) Electron blocking layer growth:

[0036] An electron blocking layer is grown by introducing trimethylaluminum and triethylgallium, with magnesia-dicyclopentadiene as the p-type doping source.

[0037] (6) Growth of the second confinement layer:

[0038] A second confinement layer is grown by introducing trimethylaluminum and triethylgallium, with magnesium bis(oxocero) as the p-type doping source;

[0039] (7) Contact layer growth:

[0040] The contact layer is grown by introducing trimethylgallium or triethylgallium, and the p-type doping source is magnesia-dicenocene.

[0041] According to a preferred embodiment of the present invention, in step (1), the growth temperature is 1000–1100°C;

[0042] In step (2), the growth temperature is 750–850℃;

[0043] In step (3), In z Ga 1-z The growth temperature of the N quantum well layer is 750–850℃, and the growth temperature of the GaN barrier layer is 800–900℃.

[0044] In step (4), the growth temperature of the second waveguide layer is 750–850℃;

[0045] In step (5), the electron blocking layer is grown at a temperature of 850–950 °C.

[0046] In step (6), the growth temperature of the second confinement layer is 850–950 °C;

[0047] In step (7), the contact layer growth temperature is 850–950℃.

[0048] The beneficial effects of this invention are as follows:

[0049] 1. This invention introduces trace amounts of aluminum atoms during the growth of the quantum well layer, suppressing the aggregation effect of indium atoms in the quantum well. This significantly improves the luminescence uniformity of the quantum well layer, reduces the full width at half maximum (FWHM) of the emission spectrum, and increases the peak gain of the laser device. Figure 4 It can be seen that the photoluminescence (PL) full width at half maximum (FWHM) of the gallium nitride green laser epitaxial wafer fabricated using this invention is reduced by 12 nm.

[0050] 2. The epitaxial structure provided by this invention can significantly reduce the threshold current of the laser, ultimately improving the output power of the device. Figure 5 It can be seen that, using the green laser of the present invention, the threshold current is reduced from 40mA to 32mA. Attached Figure Description

[0051] Figure 1 This is a schematic diagram of the structure of the present invention;

[0052] Figure 2 SIMS data plot for comparative reference sample;

[0053] Figure 3 The above are SIMS data diagrams of the inventive sample and the comparative reference sample of Embodiment 1 of the present invention.

[0054] Figure 4The full width at half maximum (FWHM) plots of the PL spectrum of the inventive sample and the comparative reference sample in Example 1 of this invention are shown.

[0055] Figure 5 The power-current curves are those of the inventive sample and the comparative reference sample of Embodiment 1 of the present invention. Detailed Implementation

[0056] The present invention will be further described below with reference to the embodiments and accompanying drawings, but is not limited thereto.

[0057] Example 1:

[0058] like Figure 1 As shown, this embodiment provides an epitaxial structure for a gallium nitride-based semiconductor laser that improves the uniformity of indium composition in a quantum well. From bottom to top, it includes a substrate, a first confinement layer, a first waveguide layer, an active region, a second waveguide layer, an electron blocking layer, a second confinement layer, and a contact layer.

[0059] The active region is In z Ga 1-z The N / GaN quantum well structure comprises three GaN barrier layers and two In... z Ga 1-z N quantum well layer, GaN barrier layer and In z Ga 1-z N quantum well layers are grown alternately, that is, each In z Ga 1-z The N-quantum well layer is flanked by GaN barrier layers, In z Ga 1-z The N quantum well layer contains Al atoms.

[0060] In z Ga 1-z The Al atom concentration in the N quantum well layer ranges from 5E18 to 5E19 / cm³. 3 The Al atomic content can be determined by secondary ion mass spectrometry (SIMS), and the atomic ratio in the crystal is about 1‰.

[0061] When the emission wavelength is blue, the active region thickness is 25-45 Å and the In composition is 0.15-0.25; when the emission wavelength is green, the active region thickness is 20-35 Å and the In composition is 0.20-0.35.

[0062] The first confinement layers, from bottom to top, are first confinement layer A and first confinement layer B. The material of first confinement layer A is Al. x1 Ga 1-x1 N, x1 is 0.01 to 0.1, thickness is 0.8 to 2 micrometers, dopant is silicon, and doping concentration is 1E18 to 1E19 / cm. 3 ;

[0063] The first confinement layer B is made of GaN with a thickness of 0.2–0.5 micrometers, and the dopant element is silicon with a doping concentration of 1E18–1E19 / cm³. 3 .

[0064] The substrate is made of gallium nitride, silicon carbide, or zinc oxide, and the substrate conductivity type is n-type.

[0065] The first waveguide layer material is In. y1 Ga 1-y1 The nitrogen (N) layer has a thickness of 0.05–0.5 micrometers and is doped with silicon at a concentration of 1E18–1E19 / cm². 3 The average value of y1 in the first waveguide layer is 0.03 to 0.08, and the indium content gradually increases, with the direction of increase from the first confinement layer to the active region. The indium content gradually increases from 0.01 to 0.06 to 0.09.

[0066] The second waveguide layer is made of In. y2 Ga 1-y2 N, with a thickness of 0.05 to 0.5 micrometers, the average value of y2 in the second waveguide layer is 0.02 to 0.07, the indium content gradually decreases, and the decreasing direction is from the active region to the second confinement layer. The indium content gradually decreases from 0.05 to 0.08 to 0.005.

[0067] The electron blocking layer material is Al x2 Ga 1-x2 The N, x2 range is 0.10–0.30, the thickness is 5–50 nm, the dopant element is magnesium, and the doping concentration is 2E18–3E19 / cm². 3 ;

[0068] The second confinement layer is made of Al material. x3 Ga 1-x3 The N, x3 range is 0.01–0.09, the thickness is 0.2–0.8 micrometers, the dopant element is magnesium, and the doping concentration is 5E17–3E19 / cm³. 3 ;

[0069] The contact layer material is GaN, with a thickness of 5–100 nanometers, and the doping element is magnesium, with a doping concentration of 2E19–1E20 / cm. 3 The fabrication method for the gallium nitride-based semiconductor laser epitaxial structure with improved indium composition uniformity in the quantum well described above includes the following steps:

[0070] (1) Growth of the first confinement layer:

[0071] Using an MOCVD device, the substrate is placed in the device, and nitrogen and hydrogen are introduced as carrier gases, while ammonia is introduced as the reaction gas to provide a nitrogen source. The temperature is raised to 1000-1100℃, and trimethylgallium and trimethylaluminum are introduced first to grow the first confinement layer A. Then, trimethylaluminum is turned off to grow the first confinement layer B. Silane is used as the n-type doping source. After the growth of the first confinement layer is completed, trimethylgallium and trimethylaluminum are turned off.

[0072] (2) Growth of the first waveguide layer:

[0073] The temperature is lowered to 750-850℃, and trimethylindium and triethylgallium are introduced. The indium composition and distribution of the first waveguide layer are controlled by the flow rate of trimethylindium or the growth temperature. When the flow rate of trimethylindium decreases, the indium composition in the waveguide layer decreases. When the growth temperature decreases, the indium composition in the waveguide layer increases. Silane is used as the n-type doping source for the confinement layer of the first waveguide layer.

[0074] (3) Growth in the active region:

[0075] Cool to 700–800°C, introduce trimethylindium and triethylgallium, and grow In. z Ga 1-z When growing the GaN quantum well layer and the GaN barrier layer, the temperature is raised to 800–900°C, and only triethylgallium is introduced. The indium composition is controlled by the flow rate of trimethylindium or the growth temperature during In growth. z Ga 1-z When using the N quantum well layer, a small amount of trimethylaluminum is introduced;

[0076] (4) Growth of the second waveguide layer:

[0077] The temperature is controlled at 750-850℃, and trimethylindium and triethylgallium are introduced to grow the second waveguide layer. The indium composition and its distribution in the waveguide layer are controlled by the flow rate of trimethylindium or the growth temperature.

[0078] (5) Electron blocking layer growth:

[0079] The temperature is raised to 850-950℃, and trimethylaluminum and triethylgallium are introduced to grow an electron blocking layer, with magnesia-diocene as the p-type doping source.

[0080] (6) Growth of the second confinement layer:

[0081] The temperature is raised to 850–950°C, and trimethylaluminum and triethylgallium are introduced to grow the second confinement layer. The p-type doping source is magnesia-diocene.

[0082] (7) Contact layer growth:

[0083] The temperature is raised to 850–950°C, and a trimethylgallium or triethylgallium contact layer is grown. The p-type doping source is magnesia-dicenocene.

[0084] Example 2:

[0085] An epitaxial structure for a gallium nitride-based semiconductor laser with improved indium composition uniformity in a quantum well is disclosed. The structure is as described in Example 1, except that the first confinement layer A has a x1 of 0.04–0.08, a thickness of 1–1.5 micrometers, and a doping concentration of 3E18–5E18 / cm. 3 ;

[0086] The thickness of the first confinement layer B is 0.2–0.3 micrometers, and the doping concentration is 3E18–5E18 / cm². 3 .

[0087] The thickness of the first waveguide layer is 0.2-0.3 micrometers;

[0088] The electron blocking layer has a x² value of 0.15–0.25 and a thickness of 8–20 nanometers.

[0089] The second confinement layer has a x3 of 0.03–0.06 μm and a thickness of 0.3–0.7 μm, with a doping concentration of 1E18–1E19 / cm². 3 ;

[0090] The contact layer thickness is 10–20 nanometers.

[0091] Comparative example:

[0092] A comparative example provides a gallium nitride-based blue-green epitaxial structure, which differs from Example 1 in that In... z Ga 1-z No aluminum atoms are introduced into the N quantum well layer, and its SIMS (secondary ion mass spectrometry) data are as follows: Figure 2 As shown, the signal of aluminum in the quantum well region is below the background noise level (<1E E17 / cm). 3 This indicates that aluminum was not intentionally introduced into the quantum well. The SIMS data of the inventive sample prepared in Example 1 are as follows: Figure 3 As shown, the aluminum atom concentration is >5E18 / cm³. 3 The concentration is much higher than the background concentration of aluminum atoms. After the epitaxial structure is grown, electrodes are fabricated on the epitaxial wafer using chip technology, the wafer is cleaved into strips and coated, the core is scratched, and finally the core is packaged onto TO5.6 for testing.

[0093] Figure 4 These are the photoluminescence (PL) curves of epitaxial wafers of the present invention and the comparative example applied to green lasers, respectively. The green laser structure fabricated using the epitaxial structure of the present invention has a emission peak half-width of 40 nm reduced to 28 nm, indicating that the quantum well indium composition of the present invention sample is more uniform.

[0094] Figure 5These are the power and current data of the present invention and the comparative example applied to green lasers respectively. The green laser made using the epitaxial structure of the present invention has a threshold current that has decreased from 40mA to 32mA and a power that has increased from 45mW to 57mW, an increase of 25%.

Claims

1. A gallium nitride-based semiconductor laser epitaxial structure for improving the uniformity of indium composition in quantum wells, characterized in that, From bottom to top, it includes a substrate, a first confinement layer, a first waveguide layer, an active region, a second waveguide layer, an electron blocking layer, a second confinement layer, and a contact layer. The active region is In z Ga 1-z The N / GaN quantum well structure comprises three GaN barrier layers and two In... z Ga 1-z N quantum well layer, GaN barrier layer and In z Ga 1-z N quantum well layers are grown alternately, that is, each In z Ga 1-z The N-quantum well layer is flanked by GaN barrier layers, In z Ga 1-z The N quantum well layer contains Al atoms; In z Ga 1-z The Al atom concentration in the N quantum well layer ranges from 5E18 to 5E19 / cm³. 3 ; When the emission wavelength is blue, the active region thickness is 25-45 Å and the In composition is 0.15~0.25; when the emission wavelength is green, the active region thickness is 20-35 Å and the In composition is 0.20~0.

35. The first confinement layers, from bottom to top, are first confinement layer A and first confinement layer B. The material of first confinement layer A is Al. x1 Ga 1-x1 N, x1 is 0.01~0.1, thickness is 0.8~2 micrometers, dopant element is silicon, doping concentration is 1E18~1E19 / cm 3 ; The first confinement layer B is made of GaN with a thickness of 0.2~0.5 micrometers, and the dopant element is silicon with a doping concentration of 1E18~1E19 / cm³. 3 ; The first confinement layer A has a x1 of 0.04~0.08, a thickness of 1~1.5 micrometers, and a doping concentration of 3E18~5E18 / cm. 3 ; The thickness of the first confinement layer B is 0.2~0.3 micrometers, and the doping concentration is 3E18~5E18 / cm. 3 ; The substrate is gallium nitride, silicon carbide, or zinc oxide, and the substrate conductivity type is n-type. The first waveguide layer material is In. y1 Ga 1-y1 N, with a thickness of 0.05~0.5 micrometers, is doped with silicon at a concentration of 1E18~1E19 / cm. 3 The average value of y1 in the first waveguide layer is 0.03~0.08, and the indium content gradually increases, with the direction of increase from the first confinement layer to the active region. The indium content gradually increases from 0.01 to 0.06~0.

09. The second waveguide layer is made of In. y2 Ga 1-y2 N, with a thickness of 0.05~0.5 micrometers, the average value of y2 in the second waveguide layer is 0.02~0.07, the indium content gradually decreases, and the decreasing direction is from the active region to the second confinement layer. The indium content gradually decreases from 0.05~0.08 to 0.

005. The electron blocking layer material is Al x2 Ga 1-x2 The N, x2 range is 0.10~0.30, the thickness is 5~50 nm, the doping element is magnesium, and the doping concentration is 2E18~3E19 / cm³. 3 ; The second confinement layer is made of Al material. x3 Ga 1-x3 The N, x3 range is 0.01~0.09, the thickness is 0.2~0.8 micrometers, the doping element is magnesium, and the doping concentration is 5E17~3E19 / cm³. 3 ; The contact layer material is GaN, with a thickness of 5-100 nanometers, and the doping element is magnesium with a doping concentration of 2E19-1E20 / cm³. 3 .

2. The gallium nitride-based semiconductor laser epitaxial structure for improving the uniformity of indium composition in quantum wells as described in claim 1, characterized in that, The thickness of the first waveguide layer is 0.2-0.3 micrometers; The electron blocking layer has a x2 of 0.15~0.25 and a thickness of 8~20 nanometers; The second confinement layer has a x3 of 0.03–0.06 μm and a thickness of 0.3–0.7 μm, with a doping concentration of 1E18–1E19 / cm². 3 ; The contact layer thickness is 10~20 nanometers.

3. The method for fabricating a gallium nitride-based semiconductor laser epitaxial structure with improved indium composition uniformity in a quantum well as described in claim 2, characterized in that, The steps are as follows: (1) Growth of the first confinement layer: Using an MOCVD device, the substrate is placed in the device, and nitrogen and hydrogen are introduced as carrier gases, while ammonia is introduced as a reaction gas to provide a nitrogen source. First, trimethylgallium and trimethylaluminum are introduced to grow the first confinement layer A; then trimethylaluminum is turned off to grow the first confinement layer B. Silane is used as an n-type doping source. After the growth of the first confinement layer is completed, trimethylgallium and trimethylaluminum are turned off. (2) Growth of the first waveguide layer: Trimethylindium and triethylgallium are introduced, and the indium composition and distribution of the first waveguide layer are controlled by the flow rate of trimethylindium or the growth temperature. When the flow rate of trimethylindium decreases, the indium composition in the waveguide layer decreases, and when the growth temperature decreases, the indium composition in the waveguide layer increases. The first waveguide layer confinement layer uses silane as an n-type dopant source. (3) Growth in the source region: Indium is grown by introducing trimethylindium and triethylgallium. z Ga 1-z In the N-quantum well layer, during the growth of the GaN barrier layer, only triethylgallium is introduced. The indium composition is controlled by the flow rate of trimethylindium or the growth temperature during In growth. z Ga 1-z When the N quantum well layer is in place, trimethylaluminum is introduced; (4) Growth of the second waveguide layer: A second waveguide layer is grown by introducing trimethylindium and triethylgallium. The indium composition and its distribution in the waveguide layer are controlled by the flow rate of trimethylindium or the growth temperature. (5) Electron blocking layer growth: An electron blocking layer is grown by introducing trimethylaluminum and triethylgallium, with magnesia-dicyclopentadiene as the p-type doping source. (6) Growth of the second confinement layer: A second confinement layer is grown by introducing trimethylaluminum and triethylgallium, with magnesium bis(oxocero) as the p-type doping source; (7) Contact layer growth: The contact layer is grown by introducing trimethylgallium or triethylgallium, and the p-type doping source is magnesia-dicenocene.

4. The method for fabricating a gallium nitride-based semiconductor laser epitaxial structure with improved indium composition uniformity in a quantum well as described in claim 3, characterized in that, In step (1), the growth temperature is 1000~1100℃; In step (2), the growth temperature is 750~850℃; In step (3), In z Ga 1-z The growth temperature of the N quantum well layer is 750~850℃, and the growth temperature of the GaN barrier layer is 800~900℃. In step (4), the growth temperature of the second waveguide layer is 750~850℃; In step (5), the electron blocking layer is grown at a temperature of 850~950℃; In step (6), the growth temperature of the second confinement layer is 850~950℃; In step (7), the contact layer growth temperature is 850~950℃.

Citation Information

Patent Citations

  • Semiconductor laser with InN phase separation suppression layer

    CN116598893A

  • Same-temperature growth method of laser quantum well active region on gallium nitride native substrate

    CN104617487A

  • Epitaxial growth of p-type cladding regions using nitrogen gas for a gallium and nitrogen containing laser diode

    US9564736B1